Immunohistochemical markers and the clinical course of adenosarcoma: a series of seven cases - Makiko Omi; Akiko Tonooka; Tomohiro Chiba; Yuji Tanaka; Atsushi Fusegi; Yoichi Aoki; Hidetaka Nomura; Hiroyuki Kanao; Yutaka Takazawa (BMC, 2020)
Abstract Background Uterine adenosarcoma, a rare uterine tumor subtype, is a biphasic tumor consisting of epithelial and mesenchymal elements. To date, there is no research comparing the histopathological features and immunohistochemistry of primary and recurrent tumors; furthermore, the relationship between pathology and the clinical course remains unclear. We reviewed the pathology and immunohistochemical features of patients with adenosarcoma and investigated the relevance of the histomorphological features to the clinical course. We also compared the immunohistochemical features of the primary and recurrent tumors. Methods The data of seven patients with adenosarcoma who underwent surgery in our hospital were evaluated. We performed immunohistochemical staining for the progesterone receptor, estrogen receptor, p53, and two Switch/Sucrose Non-Fermentable chromatin remodeling proteins (SMARCA4, BCOR), which were recently developed for the undifferentiated sarcoma diagnosis in addition to conventional staining methods. Results All patients had International Federation of Gynecology and Obstetrics stage IB-IC diseases. All tumors were polypoid and every patient presented with abnormal uterine bleeding. Six patients aged over 50 years and were menopausal; one patient aged under 50 years and was non-menopausal (average age: 59.1 years). Histologically, the sarcomatous components were homologous and heterogenous in six and one patient, respectively. Four and three cases were recurrent and non-recurrent, respectively. The recurrent patients showed high-grade morphology with sarcomatous overgrowth and were negative for ER and PR. Three recurrences could be evaluated by imaging, showing recurrence only in a distant area; biopsy specimens from these tissues revealed the identical mesenchymal component found in the primary tumor without a benign epithelial component. Immunohistochemical staining results were also similar to the corresponding of the original tumor, except for the p53 expression in one patient. At the primary site, p53 was overexpressed in two recurrent patients and had a wild-type level in one recurrent patient; however, all three recurrent tissues showed p53 overexpression. None of our patients showed SMARCA4 loss, and BCOR expression was positive in one case. Conclusions Initial pathological adenosarcoma analysis with appropriate immunohistochemical staining is vital for prognostic assessment. p53 expression might increase at recurrence. SMARCA4 and BCOR might not be an index of malignancy.